2012
DOI: 10.3176/tr.2012.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Adaption to Estonian Children of the Protocol for Cross-Cultural Research in Singing

Abstract: A Test Battery created in Canada, aimed at mapping the musical development of children of different ages and in different cultures, was piloted within a group of Estonian children (N = 26, age 4 to 12 years) with varying degrees of musical training. The verbal parts of the test were translated into Estonian and adapted, where necessary, to the temporal structure of the sub-tasks involving rhythmic and metric aspects. Participants were able to successfully comply with the majority of the test components. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…Although most of the successful performances fulfilled this expectation and had an original melody and lyrics, there were also other ways for children to execute this task: there were presentations of already known songs, of only a melody with non-meaningful syllables, and of only lyrics (poem citation). We had a similar division of results in this task as in our pilot testing with the ATBSS (Raju & Ross, 2012), and we concluded that the reason may lie in the Estonian language. In the Estonian language, the word ‘song’ ( laul ) does not have a specifically musical meaning, as it is used to indicate poems in oral or written form, epic texts, or even stories alongside singing in its narrower sense.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Although most of the successful performances fulfilled this expectation and had an original melody and lyrics, there were also other ways for children to execute this task: there were presentations of already known songs, of only a melody with non-meaningful syllables, and of only lyrics (poem citation). We had a similar division of results in this task as in our pilot testing with the ATBSS (Raju & Ross, 2012), and we concluded that the reason may lie in the Estonian language. In the Estonian language, the word ‘song’ ( laul ) does not have a specifically musical meaning, as it is used to indicate poems in oral or written form, epic texts, or even stories alongside singing in its narrower sense.…”
Section: Discussionsupporting
confidence: 66%
“…The test battery consists of 11 components addressing the different developmental aspects of musical and vocal abilities: (1) opening conversation, (2) determining the vocal range of the participant, (3) singing back a minor third, (4) singing/learning (if necessary) “Brother John” by phrases, (5) singing a favorite song, (6) singing back intervals, triads and scales, (7) improvising an ending to a melody, (8) inventing a song based on a picture, (9) singing back an unfamiliar song, (10) singing “Brother John” from memory, (11) closing conversation. The test battery was translated into Estonian, adapted to the local culture, and piloted in 2010 with 26 children (Raju & Ross, 2012). As the types of musical tasks in the test battery are generally used in music education in Estonia and are therefore familiar to children, there were no major changes made to the test battery after the pilot process.…”
Section: Methodsmentioning
confidence: 99%
“…Children were tested on the full ATBSS (Cohen, 2012; Cohen et al, 2009; Raju & Ross, 2012), which was translated into Portuguese and adapted for the Brazilian context by the first author. Children were also asked to sing the well-known “Happy Birthday” song, which has been used in several earlier research projects (e.g., Mang, 2006; Pfordresher, Brown, Meyer, Belik & Liotti, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Singing is a universal human activity that is considered to be one of the most natural means of human expression (Lomax, 1968; Nettl, 2015). For example, children have a natural tendency to sing spontaneously early in development (Dalla Bella, Giguère, & Peretz, 2007), and several studies have sought to analyze the products of children’s vocal improvisations (e.g., Campbell, 1998; Cohen, 2011; Moog, 1976; Moorhead & Pond, 1978; Raju & Ross, 2012; Raju et al, 2015; Sundin, 1997; Young, 2002). Even though singing begins naturally as a process of vocal play during the early years of life, not all individuals continue to sing or make music after childhood (Nordoff & Robbins, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Examples of dependent measures used to represent musical structure in these studies have included note entropy and the proportion of diatonic pitch classes (Goldman, 2013), the number of repeated intervals and rhythmic patterns (Norgaard, 2014), and the statistical distribution of tone choices across metrically salient beats (Järvinen, 1995). Although studies like these represent important approaches to examining musical improvisation in their own right, few attempts have been made to analyze improvisational products in a more holistic and multivariate manner, most especially with methods that do not require transcription (see Hickey & Lipscomb, 2006; Madura Ward-Steinman, 2008; Raju & Ross, 2012).…”
mentioning
confidence: 99%